Halal Products in Context of the Effect of Product Quality and Menu Variety on Purchase Decisions - Yennyka Leilasariyanti; Reny Andriyanty; H. MR. Ulung Sembiring; Sri Sugiarti; Erina Alimin (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to describe and analyze the health level of savings and loan cooperatives, namely Capital (capital), Assets (quality of productive assets), Management (management), Earning (profitability), Liquidity (liquidity). The research was conducted at KSP Kopdit Pintu Air Sikka Regency NTT. This type of research is a type of quantitative descriptive research. The data used are financial statements for 2020, 2021 and also the results of interviews from cooperative administrators. While the data analysis technique uses data analysis techniques using the Camel method. This shows that the financial performance of KSP Kopdit Pintu Air using the ratio of the Camel method is in an unhealthy situation, but in 2021 it is slightly healthier or in the moderate category.